Acinetobacter baumannii Global Clone-Specific Resistomes Explored in Clinical Isolates Recovered from Egypt - Samira M. Hamed; Walid F. Elkhatib; Hanka Brangsch; Ahmed S. Gesraha; Shawky Moustafa; Dalia F. Khater; Mathias W. Pletz; Lisa D. Sprague; Heinrich Neubauer; Gamal Wareth (MDPI AG, 2023)
Acinetobacter baumannii (A. baumannii) is a highly problematic pathogen with an enormous capacity to acquire or upregulate antibiotic drug resistance determinants. The genomic epidemiology and resistome structure of 46 A. baumannii clinical isolates were studied using whole-genome sequencing. The isolates were chosen based on reduced susceptibility to at least three classes of antimicrobial compounds and were initially identified using MALDI-TOF/MS, followed by polymerase chain reaction amplification of blaOXA-51-like genes. The susceptibility profiles were determined using a broth microdilution assay. Multi-, extensive-, and pan-drug resistance was shown by 34.8%, 63.0%, and 2.2% of the isolates, respectively. These were most susceptible to colistin (95.7%), amikacin, and trimethoprim/sulfamethoxazole (32.6% each), while only 26.1% of isolates were susceptible to tigecycline. In silico multi-locus sequence typing revealed 8 Pasteur and 22 Oxford sequence types (STs) including four novel STs (STOxf 2805, 2806, 2807, and 2808). The majority of the isolates belonged to Global Clone (GC) 2 (76.4%), GC5 (19.6%), GC4 (6.5%), GC9 (4.3%), and GC7 (2.2%) lineages. An extensive resistome potentially conferring resistance to the majority of the tested antimicrobials was identified in silico. Of all known carbapenem resistance genes, blaOXA-23 was carried by most of the isolates (69.6%), followed by ISAba1-amplified blaADC (56.5%), blaNDM-1 and blaGES-11 (21.7% each), and blaGES-35 (2.2%) genes. A significant correlation was found between carbapenem resistance and carO mutations, which were evident in 35 (76.0%) isolates. A lower proportion of carbapenem resistance was noted for strains possessing both blaOXA-23- and blaGES-11. Amikacin resistance was most probably mediated by armA, aac(6')-Ib9, and aph(3')-VI, most commonly coexisting in GC2 isolates. No mutations were found in pmrABC or lpxACD operons in the colistin-resistant isolates. Tigecycline resistance was associated with adeS (N268Y) and baeS (A436T) mutations. While the lineage-specific distribution of some genes (e.g., blaADC and blaOXA-51-like alleles) was evident, some resistance genes, such as blaOXA-23 and sul1, were found in all GCs. The data generated here highlight the contribution of five GCs in A. baumannii infections in Egypt and enable the comprehensive analysis of GC-specific resistomes, thus revealing the dissemination of the carbapenem resistance gene blaOXA-23 in isolates encompassing all GCs.